WHICH MODEL OF ECONOMIC DEVELOPMENT IS THE BEST FOR SERBIA - Aničić, Jugoslav; Aničić, Dušan (Journal of process management and new technologies, 2019)
The neoliberal model of economic development implemented by the most developed countries of the West in the recent years has caused great financial world crisis; it also led to a slow-down in the world economic growth as well as huge social inequality in the world. On the other hand, certain countries, with China as a distinct representative, have been developing their economies independently, according to the tradition and their own experience, where the government institutions, in addition to the market, have an important role in the issues of economic development. Transition countries, Serbia among them, have mainly accepted the neoliberal model of development, with an even greater lag behind the world most developed countries as a result. This paper indicates the need for the implementation of individual models of economic development, based on the specific development potentials and adjusted to the countries‘ conditions. It is better to introduce social and economic reforms gradually, in order to achieve rapid and sustainable economic development, according to the appropriate opportunities, rather than follow the trends blindly and implement reforms at any cost.